Terror from the extreme right - Bjørgo, Tore; Bjørgo, Tore (Cass series on political violence, 1995)
Right-wing terrorism in a comparative perspective: the case of split delegitimization / Ehud Sprinzak -- Right-wing violence in North America / Jeffrey Kaplan -- Radical right parties in Europe and anti-foreign violence: a comparative essay / Peter H. Merkl -- Racist violence and criminal behaviour in Sweden: myths and reality / Hel(c)♭ne L(c)œ(c)œw -- Development, patterns and causes of violence against foreigners in Germany: social and biographical characteristics of perpetrators and the process of escalation / Helmut Willems -- Extreme nationalism and violent discourses in Scandinavia: 'the resistance', 'traitors', and 'foreign invaders' / Tore Bj(c)ırgo -- Italian neo-fascist terrorism: a comparative perspective / Leonard Weinberg -- Right-wing terrorism in South Africa / David Welsh -- Wrapping up in something long: intimidation and violence by right-wing groups in postwar Japan / Kenneth Szymkowiak and Patricia G. Steinhoff